Syekh Yusuf Al-Makassari: Berawal dari Pengasingan Hingga Menjadi Tokoh Penyebar Agama Islam di Afrika Selatan - Riyan Kurniawan; Hera Tarisa; Pristi Suhendro Lukitoyo (Jurnal Ilmiah Dikdaya, 2023)
In South Africa at this time, the majority of Muslims are in the Western Cape, Natal and Transvaal regions with a diverse population ranging from Malays, Indonesians, Indians to South African Indigenous people. . Syekh Yusuf was a pioneer in the spread of Islam in South Africa, the spread of Islam carried out by Syekh Yusuf was carried out by preaching in secret to foster a sense of fate regardless of anything.